Working Long Hours and Having No Choice : Time Poverty in Guinea - Bardasi, Elena (2012)
This paper provides a new definition of 'time poverty' as working long hours and having no choice to do otherwise. An individual is time poor if he/she is working long hours and is also monetary poor, or would fall into monetary poverty if he/she were to reduce his/her working hours below a given time poverty line. Thus being time poor results from the combination of two conditions. First, the individual does not have enough time for rest and leisure once all working hours (whether spent in the labor market or doing household chores such as cooking, and fetching water and wood) are accounted for. Second, the individual cannot reduce his/her working time without either increasing the level of poverty of his/her household (if the household is already poor) or leading his/her household to fall into monetary poverty due to the loss in income or consumption associated with the reduction in working time (if the household is not originally poor). The paper applies the concepts of the traditional poverty literature to the analysis of time poverty and presents a case study using data for Guinea in 2002-03. Both univariate and multivariate results suggest that women are significantly more likely to be time poor than men.